Visa em Debate 2021
DOI: 10.22239/2317-269x.01453
|View full text |Cite
|
Sign up to set email alerts
|

Registro e perfil ecotoxicológico de produtos para controle de Aedes aegypti

Abstract: Introdução: Arboviroses transmitidas pelo Aedes aegypti têm grande relevância para a saúde pública, sendo o controle químico do vetor uma importante estratégia de mitigação. Entretanto, o uso intensivo de pesticidas está associado a seleção de insetos resistentes e impacto ambiental. Por isso, é essencial desenvolver e regulamentar novos produtos, eficazes e sustentáveis. Objetivo: Descrever os requisitos para regulação de inseticidas e repelentes no Brasil, à luz de orientações internacionais. Comparar os at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…However, several studies have reported the harmful effects associated with using DEET-based repellents, including skin irritation, encephalopathy in children, and allergic reactions [ 5 , 6 ]. This predicament has prompted agrochemical businesses and researchers to look for natural compounds and extracts that could serve as viable replacements [ 7 , 8 ]. Plants are considered a potential resource for mosquito control [ 9 ] and offer an eco-friendly approach to preventing the spread of mosquito-borne diseases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported the harmful effects associated with using DEET-based repellents, including skin irritation, encephalopathy in children, and allergic reactions [ 5 , 6 ]. This predicament has prompted agrochemical businesses and researchers to look for natural compounds and extracts that could serve as viable replacements [ 7 , 8 ]. Plants are considered a potential resource for mosquito control [ 9 ] and offer an eco-friendly approach to preventing the spread of mosquito-borne diseases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies are being developed and employed for population control of this species, aiming to reduce the cases of these diseases Zara et al, 2016;Brasil, 2019). The most commonly used method is chemical control, which uses insecticides, mainly pyrethroids, to control insect populations, especially in adulthood (Magalhães;Silva;Espindola, 2021). Biological control includes the use of predators, pathogens or genetic modifications in male mosquitoes, aiming to reduce the vector population, interrupt the transmission of the agents that cause these diseases or generate offspring that do not reach adulthood (Magalhães;Silva;Espindola, 2021).…”
Section: Introductionmentioning
confidence: 99%